2022
DOI: 10.1177/23743735221074170
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Support and its Effects on Treatment Compliance and Quality of Life in Cardiac Patients

Abstract: Background: The benefits of social support are often overlooked in common management components of cardiovascular diseases. The Multidimensional Scale of Perceived Social Support (MSPSS) is self-administered and scores perceived social support (PSS). We sought to identify PSS among cardiovascular patients and the effects it may have on quality of life (QoL) and treatment compliance. Methods: A total of 96 patients were evaluated using the MSPSS in 3 categories: significant other (SO), family, and friends using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 20 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Although it has been proven that the existence of one or more cardiovascular diseases has a negative impact on functional capacity (Arena et al 2014;Forman et al 2017;Fuentes-Abolafio et al 2020) and participation in social activities (Piepoli et al 2019), most often through the mechanisms of a reduction in physical strength, lack of self-confidence, difficulties with coping and the need for the daily intake of numerous medications (Leeming et al 2014), the availability of informal social support (i.e., from the spouse, relatives or neighbors) can reduce the negative effects of the aforementioned factors. A study by Wenn et al (2022) confirmed that the availability of social support significantly affected the quality of life of patients with heart diseases, encourages compliance with therapeutic measures and the avoidance of negative health behaviors.…”
Section: Discussionmentioning
confidence: 95%
“…Although it has been proven that the existence of one or more cardiovascular diseases has a negative impact on functional capacity (Arena et al 2014;Forman et al 2017;Fuentes-Abolafio et al 2020) and participation in social activities (Piepoli et al 2019), most often through the mechanisms of a reduction in physical strength, lack of self-confidence, difficulties with coping and the need for the daily intake of numerous medications (Leeming et al 2014), the availability of informal social support (i.e., from the spouse, relatives or neighbors) can reduce the negative effects of the aforementioned factors. A study by Wenn et al (2022) confirmed that the availability of social support significantly affected the quality of life of patients with heart diseases, encourages compliance with therapeutic measures and the avoidance of negative health behaviors.…”
Section: Discussionmentioning
confidence: 95%
“…CVDs encompass various conditions requiring long-term self-care. Compared to other CVDs, coronary heart disease, also called coronary artery disease (CAD) or ischemic heart disease (IHD), and heart failure require greater lifestyle modifications ( Wenn et al, 2022 ). According to the Mayo Clinic (2022) and the Centers for Disease Control and Prevention (2021) , coronary artery disease can lead to symptoms such as chest pain (angina), heart attack (myocardial infarction), and eventually heart failure.…”
mentioning
confidence: 99%